The interaction between competition law and corporate governance : opening the 'black box' / Florence Thépot. - Thépot, Florence (Global competition law and economics policy., 2019)
Florence Thépot provides the first systematic account of the interaction between competition law and corporate governance. She challenges the 'black box' conception of the firm- or 'undertaking' - in competition law, as applied to increasingly complex corporate relations. The book opens the 'black box' of the firm to understand the internal drivers of collusive behaviour, and proposes a unified approach to cartel enforcement, based on the agency theory. It explores key issues including corporate compliance programmes, the attribution of liability in corporate groups, and structural links between competitors, and should be read by anyone interested in how the evolution of the corporate landscape impacts competition law.